MRI-based registration of pelvic alignment affected by altered pelvic floor muscle characteristics - Bendová, Petra; Růžička, Pavel; Peterová, Věra; Fričová, Martina; Palaščáková Špringrová, Ingrid (Clinical biomechanics, 2007)
BACKGROUND: Pelvic floor muscles have potential to influence relative pelvic alignment. Side asymmetry in pelvic floor muscle tension is claimed to induce pelvic malalignment. However, its nature and amplitude are not clear. There is a need for non-invasive and reliable assessment method. An intervention experiment of unilateral pelvic floor muscle activation on healthy females was performed using image data for intra-subject comparison of normal and altered configuration of bony pelvis. METHODS: Sequent magnetic resonance imaging of 14 females in supine position was performed with 1.5 T static body coil in coronal orientation. The intervention, surface functional electrostimulation, was applied to activate pelvic floor muscles on the right side. Spatial coordinates of 23 pelvic landmarks were localized in each subject and registered by specially designed magnetic resonance image data processing tool (MPT2006), where individual error calculation; data registration, analysis and 3D visualization were interfaced. FINDINGS: The effect of intervention was large (Cohen's d=1.34). We found significant differences in quantity (P<0.01) and quality (P=0.02) of normal and induced pelvic displacements. After pelvic floor muscle activation on the right side, pelvic structures shifted most frequently to the right side in ventro-caudal direction. The right femoral head, the right innominate and the coccyx showed the largest displacements. INTERPRETATION: The consequences arising from the capacity of pelvic floor muscles to displace pelvic bony structures are important to consider not only in management of malalignment syndrome but also in treatment of incontinence. The study has demonstrated benefits associated with processing of magnetic resonance image data within pelvic region with high localization and registration reliability.
Keywords: dospělí; kosterní svaly; interpretace obrazu počítačem; subtrakční technika; Magnetic Resonance Imaging; Female; Adult; Image Interpretation, Computer-Assisted; Subtraction Technique; ženské pohlaví; lidé; magnetická rezonanční tomografie; vylepšení obrazu; Muscle, Skeletal; Pelvis; Image Enhancement; pánevní dno; Pelvic Floor; pánev; Humans